214 Dietary Supplementation with a Combination of Valine and Isoleucine Annuls the Negative Effects of Very Low Protein Diets on Growth and Gut Development of Young Pigs. (8th October 2021) - Habibi, Mohammad; Goodarzi, Parniyan; Shili, Cedrick N N; Sutton, Julia; Wileman, Caitlyn; Kim, Dohyung Markus; Lin, Dingbo; Pezeshki, Adel
Abstract: Increased feed cost, post-weaning diarrhea, and nitrogen excretion are challenging the modern swine industry. Very low-protein (LP) diets (>4% units reduced protein) may reduce feed cost, diarrhea and nitrogen excretion; however, these diets impair growth performance of pigs despite supplementation of limiting amino acids (i.e., lysine, threonine, methionine and tryptophan). The objective of this study was to investigate the effect of valine, isoleucine and combination of both supplemented to VLP diet on growth, thermal radiation, and gut development in young pigs. Forty three-week-old weaned barrows were weighed (6.75 ± 0.14 kg) and randomly assigned to five groups (8 pigs/group) including: 1) standard diet or positive control (PC), 2) LP diet, 3) LP + valine (LPV), 4) LP + isoleucine (LPI) and 5) LP + both valine and isoleucine (LPVI) for five weeks. Daily feed intake and weekly growth characteristics were measured and weekly thermal images were captured. All pigs were euthanized at week 5 and tissue samples collected. All data were analyzed with univariate GLM followed by Tukey's post-hoc test (SPSS ® ). Compared to PC, final body weight, average daily gain, average daily protein intake and gain:feed ratio were reduced in LP group, but feeding pigs with LPVI partially or completely recovered these parameters. Pigs fed with LPVI had higher thermal radiation than those fed with PC, LP, and LPI on days 28 and 35 of study and had a greater the area under the curve for thermal radiation than LP and LPI. Duodenal villus width and crypt depth, and ileal villus height were decreased in LP relative to PC, but LPVI either partially or fully recovered these measurements. In conclusion, supplementing a combination of valine and isoleucine recovered the negative effects of very low-protein diets on growth performance and gut development, but increased the thermal radiation in weaned pigs.